Undoing homogeneity in the Nordic region : migration, difference and the politics of solidarity - Keskinen, Suvi; e; Toivanen, Mari (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2019)
This book critically engages with dominant ideas of cultural homogeneity in the Nordic countries and contests the notion of homogeneity as a crucial determinant of social cohesion and societal security. Showing how national identities in the Nordic region have developed historically around notions of cultural and racial homogeneity, it exposes the varied histories of migration and the longstanding presence of ethnic minorities and indigenous people in the region that are ignored in dominant narratives. With attention to the implications of notions of homogeneity for the everyday lives of migrants and racialised minorities in the region, as well as the increasing securitisation of those perceived not to be part of the homogenous nation, this volume provides detailed analyses of how welfare state policies, media, and authorities seek to manage and govern cultural, religious, and racial differences. With studies of national minorities, indigenous people and migrants in the analysis of homogeneity and difference, it sheds light on the agency of minorities and the intertwining of securitisation policies with notions of culture, race, and religion in the government of difference. As such it will appeal to scholars and students in social sciences and humanities with interests in race and ethnicity, migration, postcolonialism, Nordic studies, multiculturalism, citizenship, and belonging.
Part 2. Governing and negotiating differences. 5. Knowledge about Roma and Travellers in Nordic schools : paradoxes, constraints, and possibilities / Jenni Helakorpi. Introduction ; Diverse groups categorised and controlled ; Data and analysis ; Racialisation ; Silence about Roma and Travellers in the nation-states ; Conclusions : paradoxes, constraints, and possibilities in providing knowledge about minoritised groups -- 6. Problematising the urban periphery : discourses on social exclusion and suburban youth in Sweden / Magnus Dahlstedt. Introduction ; "An alternative social order" : a dominant discourse on social exclusion ; "We're en route towards a catastrophe in Sweden" : problematising the suburbs ; "Nobody cares about our rights": problematising the mechanisms of social exclusion ; "What doesn't kill you makes you stronger" : a will to make a change ; "We young ones are no longer grateful" : megaphones of change ; Concluding discussion -- 7. Welfare chauvinism at the margins of whiteness : young unemployed Russian-speakers' negotiations of worker-citizenship in Finland / Daria Krivonos. Introduction ; Welfare chauvinism, whiteness and Russian-speakers in Finland ; Methodology and ethical concerns ; "You dream of success but then you become unemployed" ; Becoming white and deserving welfare claimants ; Conclusions -- 8. Starry starry night : fantasies of homogeneity in documentary films about Kvens and Norwegian-Pakistanis / Priscilla Ringrose and Elisabeth Stubberud -- Part 3. Questioned homogeneity and secularisation. 9. From welfare to warfare : exploring the miiltarisation of the Swedish suburb / g
Includes bibliographical references and index.
Keywords: Cultural pluralism -- Scandinavia; Assimilation (Sociology) -- Scandinavia; Ethnicity -- Scandinavia; Nationalism -- Scandinavia; Solidarity -- Scandinavia; Scandinavia -- Emigration and immigration -- Social aspects; Immigrants -- Scandinavia -- Social conditions; SOCIAL SCIENCE -- General; SOCIAL SCIENCE -- Sociology -- General; Assimilation (Sociology); Cultural pluralism; Emigration and immigration -- Social aspects; Ethnicity; Immigrants -- Social conditions; Nationalism; Solidarity; Scandinavia; Electronic books; Essays; Essays